HUBUNGAN PENGETAHUAN PERAWAT TENTANG KEGAWATDARURATAN DENGAN PELAKSANAAN TRIAGE PADA PASIEN GAWAT DARURAT DI UGD RUMAH SAKIT KEBONJATI BANDUNG - Tiarmaida Sitio; Yunita Sarah Nadeak; Andi sukandi (Jurnal Kesehatan, 2023)
A hospital is a form of health facility, whether organized by the government or the community, which functions to provide basic health services or referral health services or also support health services. A hospital is a form of health facility, whether organized by the government or the community, which functions to provide basic health services or referral health services or also support health services. "This study aims to find out how nurses' knowledge about emergencies relates to the implementation of triage for emergency patients in the ER at Kebonjati Hospital, Bandung." The research method is a way to obtain scientific truth, solve problems or use scientific methods. The results of the analysis showed that respondents had good knowledge, poor knowledge. Of the five articles, the majority of respondents had good knowledge. Nurse Triage Skills in the ER. The results of the analysis of triage skills from five articles showed that in four articles the majority of respondents had good skills, in one other article the respondent had sufficient skills. Relationship between Knowledge and Triage Skills of Nurses in IG. The results of the analysis of five articles as a whole show a P value <0.05. From the five articles as a whole, it can be concluded that there is a relationship between knowledge and the triage skills of emergency room nurses.